Klassische Moderne und Zeitgenössische Kunst. (Wien : Palais Dorotheum, 1999)
Absalon, Kurt ; Adrian, Marc ; Andersen, Robin Christian ; Anzinger, Siegfried ; Avramidis, Annemarie ; Baschny, Emanuel ; Beckmann, Max ; Bednarik, Karl ; Bernstein, Martin ; Beuys, Joseph ; Bischoffshausen, Hans ; Blauensteiner, Leopold ; Brauer, Erich ; Bresslern-Roth, Norbertine ; Brown, James ; Brunner, Ferdinand ; Brus, Günter ; Chagall, Marc ; Chuikov, Ivan ; Cibulka, Heinz ; Copley, William ; Curry, Adolf ; Davie, Alan ; Dier, Erhard Amadeus ; Dine, Jim ; Dobrowsky, Josef ; Dorfer, Olivier ; Doxat, Robert ; Ebneth, Lajos von ; Eder, Otto ; Egger-Lienz, Albin ; Eisenschitz, Willi ; Ende, Wien ; Faistauer, Anton ; Fauconnier, Henri Le ; Fehlau, Fred ; Feilacher, Johann ; Fischer, Johann ; Fleck, Karl Anton ; Floch, Josef ; Flora, Paul ; Frankl, Gerhardt ; Freist, Greta ; Frieberger, Padhi ; Frohner, Adolf ; Fruhmann, Johann ; Fuchs, Ernst ; Gappmayr, Heinz ; Garber, Johann ; Gasteiger, Jakob ; Gironcoli, Bruno ; Götzinger, Hans ; Gunsam, Karl Josef ; Gurschner, Herbert ; Gutenegg, Otto zu ; Gütersloh, Albert Paris ; Hamaguchi, Yozo ; Hanak, Anton ; Harlfinger, Richard ; Harta, Felix Albrecht ; Hauser, Carry ; Hauser, Johann ; Henneberg, Hugo ; Herzmanovsky-Orlando, Fritz von ; Hessing, Gustav ; Höckelmann, Antonius ; Hoflehner, Rudolf ; Hollegha, Wolfgang ; Hrdlicka, Alfred ; Huber, Ernst ; Hundertwasser ; Hutter, Wolfgang ; Janssen, Horst ; Jorn, Asger ; jun., Carl Moser ; Jussel, Eugen ; Kabakov, Ilya ; Kádár, Bela ; Kaden, Siegfried ; Kaiser-Herbst, Carl ; Kaltenbeck, Franz ; Kaufmann, Wilhelm ; Kawabata, Minoru ; Keil, Robert ; Kitt, Ferdinand ; Klasen, Peter ; Klimt, Gustav ; Koch, Ludwig ; Koechl, Manfred ; Kokoschka, Oskar ; Kolig, Anton ; Korab, Karl ; Kozlowski, Wladislaw ; Kubin, Alfred ; Kukla, Reinhold ; Lack, Stephan ; Larwin, Hans ; etc.
Duits
boek